Innovations in Hepatitis C Screening and Treatment - Patel, Arpan A. (Hepatol Commun, 2020)
New therapies offer hope for a cure to millions of persons living with hepatitis C virus (HCV) infection. HCV elimination is a global goal that will be difficult to achieve using the traditional paradigms of diagnosis and care. The current standard has evolved toward universal HCV screening and treatment, to achieve elimination goals. There are several steps between HCV diagnosis and cure with major barriers along the way. Innovative models of care can address barriers to better serve hardly reached populations and scale national efforts in the United States and abroad. Herein, we highlight innovative models of HCV care that aid in our progress toward HCV elimination.